C and S corporation banks: Did Trump's tax reform lead to differential effects? - Hoang Ha Nguyen Thi; Alfons J. Weichenrieder (Leibniz Institute for Financial Research SAFE, 2021)
The US Tax Cuts and Jobs Act (TCJA) led to a drastic reduction in the corporate tax and improved the treatment of C corporations compared to S corporations. We study the differential effect of the TCJA on these types of corporations using key economic variables of US banks, such as the number of employees, average salaries and benefits, profit/loss before taxes, and net income. Our analysis suggests that the TCJA increased the net-of-tax profits of C corporation banks compared to S corporations and, to a lesser extent, their pre-tax profits. At the same time, the reform triggered no significantly differential effect on the employment and average wages.
Keywords: H2; G2; 330; Tax Cuts and Jobs Act; corporate taxation; S corporations; C corporations; banks